Effectiveness of a twelve-week manual therapy intervention for shoulder injury prevention and management in female volleyball players - Thenmozhi, Tamilarasu; Senthil Kumar, Murugan; Kalmykova, Yuliya; Sanjaykumar, Swamynathan; Okun, Daria (Фізична реабілітація та рекреаційно-оздоровчі технології, 2024)
Purpose: This study aimed to assess the efficacy of a twelve-week manual therapy intervention in preventing and managing shoulder injuries among female volleyball players through a randomized controlled trial. Material and Methods: Forty college female volleyball players aged 18-25 years with a history of shoulder pain or dysfunction were recruited and randomly assigned to either a manual therapy intervention group or a control group. The intervention group received a comprehensive manual therapy program, including soft tissue mobilization, joint mobilization, and tailored exercise therapy, administered by a licensed physical therapist. Outcome measures, including shoulder range of motion, strength, pain levels, functional performance, and incidence of shoulder injuries, were assessed at baseline, post-intervention (twelve weeks), and follow-up (three months post-intervention). Statistical analysis was conducted using Paired t-tests and Wilcoxon Signed-Rank Tests. Results: Significant improvements were observed in shoulder range of motion, strength, and functional performance in the intervention group compared to the control group at post-intervention and follow-up assessments. Specifically, the intervention group exhibited notable enhancements in shoulder range of motion and strength. Moreover, a significant reduction in baseline pain levels was observed among participants in the intervention group. Conclusions: The findings suggest that a comprehensive twelve-week manual therapy program holds promise in effectively addressing shoulder injuries among female volleyball players. Manual therapy techniques, including soft tissue and joint mobilization, alongside tailored exercise therapy, may serve as valuable adjuncts to traditional preventive strategies in sports injury management.